ANALISIS INTERNAL DAN EKSTERNAL PENGELOLAAN PERIKANAN PANTAI SKALA KECIL DI KOTA TEGAL (An Internal and External Analysis of Small-Scale Coastal Fisheries Management in Tegal City) - Agnes P. Sudarmo; MS. Baskoro; Budy Wiryawan; Eko S. Wiyono; Daniel R. Monintja (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2016)
ABSTRACTThe problems that occur in coastal areas related to the management of small-scale coastal fisheries in Tegal are the depletion of fish resources in coastal waters, and a variety of pressures including pressure due to population growth, abrasion as well as water pollution. A holistic understanding of internal and external factors of coastal fisheries management is needed to determine how these factors affect the fishing activities in Tegal. The purpose of this research is to analyze the internal and external factors of small-scale coastal fisheries management in Tegal. The benefit of this research is to give feedback to stakeholders and constructive actions in creating sustainable management of coastal fisheries. This study was conducted in Tegal precisely in the village of Muarareja. The sample in this study is 64 small-scale fishermen, using purposive sampling. Primary data were collected by using questionnaires, secondary data were obtained from Departementnof Agriculture and Marine Tegal, Bureau of Statistics of Tegal, Muarareja Fish Auction. Data were analyzed using descriptive analysis and SWOT analysis. The results showed that the present status of coastal fisheries management in Tegal is currently categorized as "good condition", and is still in a stable growth. There were 5 (five) alternative strategies to manage small-scale coastal fisheries management in order to improve and to enhance sustainability, namely, development of fishing gear independently, monitoring surveillance of fishing gear, utilization of fishing equipment to optimize the catch, and utilization of revolving fund for procurement of new machines.Keywords: coastal fisheries management, internal-external analysis, management-------ABSTRAKPermasalahan yang menerpa wilayah pesisir dalam pengelolaan perikanan pantai skala kecil di Kota Tegal terkait dengan adanya penurunan potensi sumber daya ikan di perairan pantai Kota Tegal, selain itu dipicu juga adanya pertumbuhan populasi penduduk, perubahan fungsi / alih lahan, pencemaran perairan, ataupun abrasi. Pemahaman yang holistik terkait faktor internal dan faktor eksternal pengelolaan perikanan pantai sangat diperlukan untuk mengetahui bagaimana faktor-faktor tersebut berpengaruh terhadap aktivitas perikanan tangkap yang ada di Kota Tegal. Tujuan penelitian adalah menganalisis faktor internal dan eksternal pengelolaan perikanan pantai di Kota Tegal. Manfaat yang diinginkan adalah memberi masukan kepada pemangku kepentingan dan tindakan konstruktif dalam menciptakan pengelolaan perikanan pantai yang berkelanjutan. Penelitian dilakukan di Tegal tepatnya di desa Muarareja. Sampel dalam penelitian ini adalah nelayan skala kecil yang berjumlah 64 orang. Pengambilan sampel dilakukan secara purposive. Jenis data yang diambil adalah data primer dengan menggunakan kuesioner sedangkan data sekunder diperoleh dari Dinas Kelautan dan Pertanian Kota Tegal, BPS Kota Tegal, Tempat Pelelangan Ikan Muarareja. Data dianalisis menggunakan analisis deskriptif dan analisis SWOT. Hasil penelitian menunjukkan kondisi terkini pengelolaan perikanan pantai di Kota Tegal saat ini termasuk kategori â€cukup baikâ€, dan masih dalam pertumbuhan yang stabil. Usulan program strategis yang terkait dengan pengelolaan perikanan pantai di Kota Tegal yaitu pengembangan alat tangkap secara mandiri, pengawasan bersama keamanan alat tangkap, optimalisasi penangkapan ikan pada saat harga jual ikan naik, pemanfaatan alat tangkap bantuan untuk optimalisasi hasil tangkapan, dan pemanfaatan dana bergulir untuk pengadaan mesin baru.Kata kunci: analisis internal-eksternal, pengelolaan perikanan pantai, manajemen